(untitled) (Journal of University of Babylon for Engineering Sciences, 2021)
To ensure the best operations situation of the wind turbine under critical conditions, a thoroughly analysis of converter controls in both machine and grid sides is essential. The grid side is playing the major role therefore its codes as stabilization, fault ride through, quality of power improving, synchronizing, controlling power and other codes must be satisfied. This paper aims to analyze the Doubly-Fed Induction Generator (DFIG). Analysis shall cover the situations: under balanced grid, under voltage sag, under voltage swell, under changes in reactive power demand and under changes in supply frequency. The system model and controlling are needed to analyze the whole DFIG system in the steady-state and transient state operations. A back to back converters are used in this system. A model of the grid converter independently controlling the active and reactive power including dc-link voltage is constructed. Machine side converter model is also built such that it is maintaining the unity power-factor and controlling reactive power regardless the transient condition of the grid. MATLAB/SIMULING models are used for this analysis.